Secular Trends in the Epidemiologic Patterns of Thyroid Cancer in China Over Three Decades: An Updated Systematic Analysis of Global Burden of Disease Study 2019 Data - Li, Yongze; Piao, Jianming; Li, Min (Frontiers in Endocrinology, 2021)
Background: Thyroid cancer is the most common malignant endocrine disease worldwide. The changing epidemiologic pattern of thyroid cancer at the national level in China has remained unknown over the last three decades. Methods: Following the general analytical strategy used in the Global Burden of Disease Study (GBD) 2019, the age- and sex-specific incidence, mortality, and prevalence rates of thyroid cancer in China were analyzed. Trends in the incidence, mortality, prevalence, and disability-adjusted life years (DALYs) due to thyroid cancer from 1990 to 2019 were assessed by joinpoint regression analysis. Age, period and cohort effects on incidence were estimated by an age-period-cohort model. Results: From 1990–2019, the age-standardized prevalence and incidence rates significantly increased in both males and females, and the age-standardized mortality rate decreased in females but increased in males. Moreover, the increments in all the age-standardized measures of thyroid cancer in China were higher in males than in females. The age effect showed that those aged 40–44 years had the highest relative risk (RR) among females, and the RR increased with age among males. The incidence increased with time and began to substantially increase in 2009. The cohort effect showed that the incidence decreased in successive birth cohorts. Conclusions: The burden of thyroid cancer in China showed unexpected patterns that varied by sex, age, and year. Notably, males had higher average annual percentage changes in thyroid cancer incidence and mortality rates than females. More attention should be given to improving the thyroid cancer burden in males in China.